Sistem Informasi Keuangan Pada Koperasi Pegawai Republik Indonesia Balaikota Payakumbuh Menggunakan Metode Single Moving Average - Nhaya Aprila Jefrina; Annisak Izzaty Jamhur (Riset Sinergi Indonesia (RISINDO), 2026)
The objective of this research is to design a web-based revenue prediction system for Koperasi Pegawai Republik Indonesia Balaikota Payakumbuh in order to facilitate better revenue planning. The planned system's goal is to help management board make more accurate, efficient, and methodical forecasts of future income using the historical data that is currently accessible. Monthly total income from the cooperative over a year are included in the data set utilized in this study, forming the foundation for the prediction method. The Single Moving Average (SMA) is the approach used by the system. It predicts revenue for the upcoming period by averaging the revenue from the previous few periods. Additionally, the Mean Absolute Percentage Error (MAPE) is used to assess the accuracy of the prediction outcomes in order to ascertain the degree of forecasting error. The testing data indicate that the constructed system achieves a MAPE value of 6.63%, which is considered to be highly accurate. These results show that the suggested system can aid management board in making more informed judgments about revenue planning for future periods.